La Didascalia Apostolorum e la giustizia del vescovo prima di Costantino - Loschiavo, Luca (Comporre il conflitto, 2020)
Scholars are long used to consider the episcopal justice beginning from the Constantine’s constitutions on the ‘episcopalis audientia’ (a.D. 318 and 333). After at least two centuries, an articulated and participated discussion is still alive concerning the nature of the episcopal courts and other aspects of its structure and its functioning (a real judicial activity or a simple arbitration; competence limited to private disputes or extended to criminal cases; relationship with imperial jurisdiction; procedural models …). Many questions remain opened and no position seems to prevail in the debate. To come out from such an empasse, it could be useful to pay attention to what happened in the ancient (pre-constantinian) Christian communities in case of a dispute between two ‘brothers’. The Gospel’s ‘paradoxical’ indications often clashed with practical difficulties. Some more ‘concrete’ suggestions came certainly from the Epistles of Paul. Much more useful must have however been for the bishops the anonymous text of the Doctrina duodecim Apostolorum better known as Didascalia Apostolorum.